Detection of Oryctomorphus bimaculatus (Coleoptera: Scarabaeidae: Rutelinae) in Platanus orientalis, Talca, Chile. (2019)
The presence of the xylophage beetle Oryctomorphus bimaculatus is recorded for the first time in a specimen of Platanus orientalis, whose age exceeded 80 years old at end of the spring of 2015 in Talca city, Chile. Several stages of the beetle were found next to a group of saprophytic fungi. The tree was revised with traditional elements and with non-destructive instruments to evaluate the amount of damage. The presence of these agents was not found in other trees in the vicinity